Distributed FlowVisor: a distributed FlowVisor platform for quality of service aware cloud network virtualisation. Issue 5 (1st September 2015) - Liao, Lingxia; Shami, Abdallah; Leung, Victor C.M.
Abstract : Cloud‐based virtual networking environments are required to provide fine‐grained quality of service (QoS) control without sacrificing scalability. However, no single approach can currently achieve these two goals simultaneously. FlowVisor is a building block to virtualise networks with fine‐grained QoS support; however, scalability issues caused by the OpenFlow protocol and the centralised control model are a major concern. This study introduces a distributed FlowVisor (DFVisor) platform to address these scalability issues. The proposed DFVisor uses a layered overlay mechanism to improve network addressing space and switch capacity. DFVisor uses a distributed synchronised two‐level database system with a synchronisation mechanism to enable the centralised control functions in the current FlowVisor platform in distributed control modules within the virtual network controllers. Therefore it removes a single point of failure in the network and reduces the flow setup latency without sacrificing the centralised network configuration and management capabilities. More importantly, the proposed DFVisor platform enables an advanced push‐based flow setup and statistics collection mechanism to address scalability issues caused by the current pull‐based flow setup and statistics collection method. A DFVisor prototype and an evaluation of this distributed synchronised two‐level database are presented, and key issues for future research are discussed.